FORMAT PENDAMPINGAN USAHA MIKRO, KECIL DAN MENENGAH UNTUK MENAIKKAN OMZET DI KECAMATAN CIPAYUNG, SUKMAJAYA, DAN PANCORAN MAS, KOTA DEPOK - Budi Suswanto (Institut Bisnis Muhammadiyah Bekasi, 2021)
In the current pandemic era, it is undeniable that Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the national economy. In the midst of many large businesses that have gone bankrupt. Even so, there are still many MSMEs that still apply conventional patterns in marketing their products. Even though consumers have changed, consumer behavior has also changed, so without realizing it, the marketing of MSME products is not optimal. One way for MSMEs to be carried out optimally is by providing business assistance. The purpose of this research is to find out the right format in assisting MSMEs to increase their business turnover and be able to expand the market. The research model used is a qualitative descriptive research model. In conclusion, business assistance by institutions or people who are experienced in business can be a perfect solution for MSMEs. However, what is quite a concern is the way of business assistance in each MSME, the method used is not always the same. It depends on the type of business being carried out, the target market segment, and the marketing area. All of this becomes a single unit in developing an existing business.